The Abinit project: impact, environment and recent developments - Gonze, Xavier; Amadon, Bernard; Antonius, Gabriel; Arnardi, Frédéric; Baguet, Lucas; Beuken, Jean-Michel; Bieder, Jordan; Bottin, François; Bouchet, Johann; Bousquet, Eric; Brouwer, Nils; Bruneval, Fabien; et al. (Computer physics communications, 2020)
Abinit is a material- and nanostructure-oriented package that implements density-functional theory (DFT) and many-bodyperturbation theory (MBPT) to find, from first principles, numerous properties including total energy, electronic structure, vibrational and thermodynamic properties, different dielectric and non-linear optical properties, and related spectra. In the special issue to celebrate the 40th anniversary of CPC, published in 2009, a detailed account of Abinit was included [Gonze et al, Comput. Phys. Comm. 180, 2582 (2009)], and has been amply cited. The present article comes as a follow-up to this 2009 publication. It i ncludes an analysis of the impact that Abinit has had, through for example the bibliometric indicators of the 2009 publication. Links with several other computational materials science projects are described. This article also covers the new capabilities of Abinit that have been implemented during the last three years, complementing a recent update of the 2009 article published in 2016. Physical and technical developments inside the abinit application are covered, as well as developments provided with the Abinit package, such as the multibinit and a-tdep projects, and related Abinit organization developments such as AbiPy . The new developments are described with relevant references, input variables, tests, and tutorials.